THE CORRELATION BETWEEN POOR ORAL HYGIENE AND ORAL HEALTH-RELATED QUALITY OF LIFE AMONG DRUG USERS: Hubungan Antara Kebersihan Gigi dan Mulut Terhadap Kualitas Hidup Pada Pengguna Narkoba - Riky Hamdani; Sitepu, Alexander; Wahyu Pertiwi, Indraswari (Jurnal Berkala Epidemiologi, 2025)
Background: The quality of life among drug users has become an increasingly important public health issue. One of the factors suspected to contribute to this is poor oral hygiene, which may result from reduced saliva production due to long-term use of psychotropic substances. This condition warrants special attention, particularly in Banjarbaru City, which has the highest rate of drug abuse in South Kalimantan Province, with a proportion of 26.64%. Purpose: The purpose of this study is to analyze the correlation between drug users' quality of life and their dental and oral hygiene. Methods: This study employed a cross-sectional design and was conducted on a representative sample of drug users undergoing rehabilitation. A total of 38 respondents were selected using a simple random sampling method. Data on dental and oral hygiene were collected using the Oral Hygiene Index Simplified, while quality of life was measured using the OHIP-14 questionnaire. The data were then analyzed using appropriate statistical methods to determine the correlation between the variables.   Results: Dental and oral hygiene for drug abusers have an average score of 3.38 and an average quality of life score of 21.25. Poor oral hygiene is associated with poor quality of life in drug abusers (r = 0.572, p-value <0.000). Regression analysis showed that poor oral hygiene was a predictor of poor quality of life (β: 3.936; R2: 0.328; p <0.000). Conclusion: This study emphasizes how crucial it is to practice proper dental hygiene in order to improve drug users' quality of life.